Insight and attitude of illness in relation to the relapse rate among schizophrenic patients in Hospital Universiti Sains and Hospital Kota Bharu - Fauzi, Radziah Mohd; Ismail, Hasanah Che (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
Background: Lack of insight in schizophrenia has p~en increasingly in focus. It is frequently reported that schizophrenic patients have poor insight towards their illness. Several rating scales were developed to measure the -insight in relation to the different important aspects. Objectives: This cross-sectional study was conducted to determine the relationship between the level of insight and attitude of illness to the relapse rataamong schizophrenic patients in Hospital Universiti Sains Malaysia and Hospital. Kota Bharu. Methods: . A total of 409 schizophrenic patients who were in· stable condition involved in this cross-sectional study. Various aspects of insight towards illness need for treatment and attribution of the symptom' were assessed with our new scale: Insight and Attitude Scale of Schizophrenia (lASS). The measurement of insight has been based on this new self-administer~d questionnaire. Results: Insight and Attitude Scale of Schizopprenia (lASS) is presented, and evidence in support of its reliability and validity is provided. The result found there is significant corr.elation between patients' insight and relapse rate. Patients with high insight are more likely to have ·less relapses compared to patients with low insight. Conclusion: The scale is a quick and acceptable measure for insight among our population. Patients_ with high insight ~co:e were significantly less likely to have relapse compared w1th those with low 1nsight scoore suggesting that insight may influence the relapse rate among schizophremc patients in the study population.